CAN THE FEELING OF BEING SAFE BE DANGEROUS?. (7th October 2012) - Hart, G
Abstract : Background: Despite great advances in safety, many people continue to come to preventable harm. It is possible that we may be investing too much effort in creating a FEELING of being safe rather than actually BEING safe. We often encounter goal-oriented language that says 'people should be free of fear.' Yet it is this sense of vulnerability that can keep us safest. Have we created environments that have counter intuitively increased risk while at the same time diminishing the feeling of risk? Aims/Objectives/Purpose: How can we make the best use of our feelings of natural risk (perhaps through a common set of principles) and calibrate the environments we design to get the best possible result—maximum safety? Can we improve people's sense of appropriate vulnerability so they have better control over their risks and are less likely to come to harm? Methods: A number of interactions were studied including traffic, workplace, home, sporting safety and suicide prevention. Contexts from hunter-gatherer societies to rural settings and on to modern urban environments were considered. Common principles were selected and analysed in each scenario. Results/Outcome: A set of common, testable principles including factors like proximity, familiarity, distraction and others were uncovered that could be employed in tuning feelings of risk in different contexts to lower the likelihood of harm occurring. Significance/Contribution to the Field: Developing and employing this approach will generate more precise calibrations of natural risk so that contexts can be designed to illicit safer outcomes while sharpening people's sense of risk.